Are The Laws for Us or Against Us? Reinventing Environmental Sanitation Laws in Nigeria - Folakemi. O Ajagunna; Opeyemi.A. Gbadegesin (Administrative and Environmental Law Review, 2023)
Environmental sanitation has been defined as managing any aspects of a man's physical environment that might harm his physical, cognitive, or social health. Indoctrinating good environmental sanitation practices into its citizenry has been and remains a foremost concern for the Nigerian government, with several laws enacted at levels of government to achieve this target. Although there are many of these laws, compliance with environmental sanitation laws remains at its lowest ebb in Nigeria. Nigeria's current environmental sanitation situation reflects that these laws are obeyed more in abeyance, with many viewing compliances as a fool's errand rather than a necessary evil. The method used in this research is descriptive and doctrinal. This paper discusses the issue of environmental sanitation in Nigeria and examines the existing legal system for achieving a cleaner Nigeria. This paper posits that having a clean Nigeria is achievable and asserts that a bottom-up approach to environmental sanitation lawmaking in Nigeria is needed to achieve this goal. A participatory community module for sanitation lawmaking is recommended to ensure that the people understand the importance of these laws by taking ownership of the process rather than depending on the government for its actualization.